2023
DOI: 10.1029/2022ef003215
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Memory of Land Surface Models Utilized in Major Reanalyses Differ Significantly From SMAP Observation

Abstract: Near-surface hydrometeorological behaviors occurring at different timescales are important for regional weather and climate (Seneviratne et al., 2010). For example, the coupling of surface water and temperature anomalies can intensify the evolutions of extreme events such as droughts and heatwaves (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The time-lag duration between FVC and climate changes was correlated with the topographical characteristics: most of the research area received a 1-2 months' time lag between FVC and PRE and TEM changes, whereas a 6 months' time lag was detected in the conjunction area of GZP, QBM, and LOP. Previous studies have shown that soil temperature and soil moisture exhibit memory effects [59,60], and climate change can affect the temperature and water content of soil. This is likely the reason for the lagged response between vegetation and climate factors.…”
Section: Discussionmentioning
confidence: 99%
“…The time-lag duration between FVC and climate changes was correlated with the topographical characteristics: most of the research area received a 1-2 months' time lag between FVC and PRE and TEM changes, whereas a 6 months' time lag was detected in the conjunction area of GZP, QBM, and LOP. Previous studies have shown that soil temperature and soil moisture exhibit memory effects [59,60], and climate change can affect the temperature and water content of soil. This is likely the reason for the lagged response between vegetation and climate factors.…”
Section: Discussionmentioning
confidence: 99%
“…θ w , θ c , and θ fc refers to soil wilting point, critical point, and field capacity, respectively. Figures adapted from (He et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…However, these improvement studies are model specific, that is to say, SM biases cannot be improved if the models already use the optimal parameterization schemes or land surface parameters. The systematical SM biases (i.e., the long‐term equilibrium SM) determined by soil texture between models should be improved through the calibration of soil texture data sets utilized in current LSMs (He et al., 2023; Teuling et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Encompassing a broader perspective, Ruscica et al (2014) assumed that anomalous soil moisture impacts the atmospheric state through complicated land surface feedback mechanisms that span across diurnal to seasonal timescales. The multifaceted nature of SMM finds expression in the explanation offered by He et al (2023), who propose two distinct but not independent descriptions: one represents the SMM as the temporal duration required for a perturbation to manifest and decay in the time domain (irreversible changes), while the second definition relates to the time taken for soil moisture to regain equilibrium following a perturbation (reversible changes). In any case, the perturbations considered so far encompass a diverse array of wet anomalies like precipitation or dry anomalies like drought.…”
Section: Conceptmentioning
confidence: 99%
“…As field capacity is used directly in the autocorrelation expression of soil moisture (Koster & Suarez, 2001;Seneviratne & Koster, 2012), it can be a good candidate for studying the effects of other soil properties on SMM. The t SMM increases with greater soil depth (Amenu et al, 2005;Asharaf & Ahrens, 2013;Douville et al, 2007;He et al, 2023;MacDonald & Huffman, 2004;Martínez-Fernández et al, 2021;Ruscica et al, 2014;Song et al, 2019;Wu et al, 2002), as deeper layers exhibit higher organic and clay contents (Martínez-Fernández et al, 2021), larger magnitudes of soil moisture spectra (Asharaf & Ahrens, 2013), and slower drying times after precipitation events. 3.…”
Section: Reviews Of Geophysicsmentioning
confidence: 99%